Percutaneous Coronary Intervention or Minimally Invasive Coronary Bypass for Isolated Left Anterior Descending Artery Disease - Gallingani, Alan; Pampuri, Giulia; Diab, Nadim; Grassa, Giulia; Hernandez-Vaquero, Daniel; Tuttolomondo, Domenico; Carino, Davide; Singh, Gurmeet; Nicolini, Francesco; Formica, Francesco (The American journal of cardiology, 2025)
The optimal revascularization strategy for isolated left anterior descending (LAD) artery disease, minimally invasive direct coronary artery bypass (MIDCAB) and percutaneous coronary intervention (PCI), remains a subject of debate. This updated meta-analysis aimed to compare the long-term outcomes of MIDCAB versus PCI for patients with isolated LAD artery disease. Three databases were systematically searched to identify randomized controlled trials (RCTs) and adjusted studies. Primary outcomes included long-term survival and repeat target vessel revascularization (TVR). The secondary endpoint was long-term major adverse cardiovascular events (MACEs). Hazards ratios (HR) and Confidence Intervals (CI) were calculated for long-term outcomes and a random effects model was used. Sensitivity analyses included subgroups analysis of stent-type. Nine articles, comprising 4 RCTs, totaling 2,168 patients (MIDCAB = 1,086 and PCI = 1,080) were included. The weighted mean follow-up was 4.35 ± 4.9 years. Long-term survival was comparable between MIDCAB and PCI (HR = 0.76; 95% CI, 0.58 to 1.00; p = 0.05). MIDCAB was associated with a significantly lower rate of repeat TVR (HR = 0.35; 95% CI, 0.25 to 0.49; p <0.0001) and a reduced risk of MACEs (HR = 0.59; 95% CI, 0.43 to 0.81; p <0.0001), although the difference was not evident in subgroup analysis comparing MIDCAB and PCI with drug-eluting stent (HR = 0.66; 95% CI, 0.46 to 1.06; p = 0.09). In conclusion, this meta-analysis of RCTs and adjusted studies shows that in patients with isolated LAD lesion, MIDCAB and PCI exhibit comparable long-term survival. However, MIDCAB is associated with a significantly reduced risk of long-term repeat TVR and MACEs compared to PCI.